IMPLEMENTASI HUKUM PELAYANAN KESEHATAN GIGI PADA ANAK PENYANDANG RETARDASI MENTAL DI SLB C YPAC KOTA SEMARANG - Edi Sumarwanto; Nendika Dyah Ayu; Septi Duvasti Kurnia Illahi (Universitas Baiturrahmah, 2023)
Introduction: Mental retardation, characterized by an index IQ less than 70, causes limitations in motoric skills such as brushing teeth. The inability to brush their teeth will affect their oral health, which can increase various oral diseases; hence, children with mental retardation need affirmative action. Aim: The purpose of this study was to determine the implementation of the law regarding dental health services for children with mental retardation at SLB C YPAC Semarang. Methods: The method of the research is a qualitative method with a juridical-sociological approach. The data used in the primary data are from interviews with the pediatric dentist, director of the hospital, SLB teachers, principal, and jurist. Secondary data are from literature studies that support the primary data. Result: The existing regulation only gives an obligation for the government to fulfill. If they are not implementing the regulation, there is no reporting mechanism or regulatory sanctions. In practice, the right to obtain socialization or information about the dental health of children with mental retardation, the right to access facilities and paramedics without discrimination, and the right to get affirmative action such as dental team service, communication, visitation hours, a dental chair, and treatment specifically stated in the regulation of the Minister of Health Number 89 of 2015 on dental and oral health efforts are not based on that regulation. Conclusion: Without any sanctions, the existing regulation has not been able to guarantee compliance with the right to dental health for children with mental retardation. Therefore, it is still not sufficient as a basis for compliance with human rights